Geopolitik Digital dalam Sistem Pembayaran QRIS: Analisis Resistensi Indonesia terhadap Hegemoni Keuangan Global - Imama Zuchroh; Setiyawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the dynamics of digital geopolitics in the Quick Response Code Indonesian Standard (QRIS) payment system as a form of Indonesia's resistance against the United States' global financial hegemony. Using descriptive qualitative research methods with a library research approach, this study examines the United States' criticism of QRIS in the National Trade Estimate 2025 report and Indonesia's response. The research findings indicate that QRIS represents Indonesia's digital sovereignty strategy that challenges the dominance of US-based global payment systems. US criticism of QRIS, which is considered to limit foreign companies' access, actually strengthens Indonesia's digital nationalism narrative. QRIS implementation has reached 56.3 million users with 38.1 million MSMEs in the first quarter of 2025, demonstrating the success of digital financial inclusion. The expansion of QRIS to Japan, China, and other Asian countries starting in August 2025 proves that Indonesia has successfully built an alternative payment system that does not depend on Western financial infrastructure. Indonesia's resistance to US pressure through QRIS marks a transformation from object to subject in the global financial architecture, while strengthening Indonesia's position as a regional digital power.